2010
DOI: 10.1063/1.3284787
|View full text |Cite
|
Sign up to set email alerts
|

Design and validation of a novel bioreactor principle to combine online micro-computed tomography monitoring and mechanical loading in bone tissue engineering

Abstract: Mechanical loading plays an important role in bone remodeling in vivo and, therefore, has been suggested as a key parameter in stem cell-based engineering of bone-like tissue in vitro. However, the optimization of loading protocols during stem cell differentiation and subsequent bone-like tissue formation is challenged by multiple input factors, which are difficult to control and validate. These include the variable cellular performance of cells harvested from different patients, nonstandardized culture media … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…According to specific study objectives, a customized strategy will be required to extract the necessary information in a robust way, ranging from (1) accurate and detailed (100s of mm scale) identification and quantification of different TE construct components limited to small TE construct samples and using phase-contrast imaging, 25 to (2) using standard desktop micro-or nano-CT as a routine 3D imaging technique for whole TE construct analysis (mm to cm scale) and quantification of mineralization after in vivo implantation. 10,13 The latter approach, without the use of a contrast agent, has also been used for static or bioreactor in vitro cultures, 16,18,19 showing distinct contrast differences between the mineralized matrix and scaffold. Phase-contrast imaging [24][25][26] or micro-CT combined with osmium tetroxide as a contrast agent 28 has shown its potential to assess nonmineralized ECM in an in vitro engineered TE construct.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to specific study objectives, a customized strategy will be required to extract the necessary information in a robust way, ranging from (1) accurate and detailed (100s of mm scale) identification and quantification of different TE construct components limited to small TE construct samples and using phase-contrast imaging, 25 to (2) using standard desktop micro-or nano-CT as a routine 3D imaging technique for whole TE construct analysis (mm to cm scale) and quantification of mineralization after in vivo implantation. 10,13 The latter approach, without the use of a contrast agent, has also been used for static or bioreactor in vitro cultures, 16,18,19 showing distinct contrast differences between the mineralized matrix and scaffold. Phase-contrast imaging [24][25][26] or micro-CT combined with osmium tetroxide as a contrast agent 28 has shown its potential to assess nonmineralized ECM in an in vitro engineered TE construct.…”
Section: Discussionmentioning
confidence: 99%
“…Fluid flow is known to enhance matrix synthesis within TE constructs during perfusion culture. 19,40,50 Furthermore, differences in fibrillar collagen organization of the ECM, which are flow dependent, 51 could also explain the ECM differences that were observed by PTA staining as the ECM morphology could influence the binding mechanism of PTA to the ECM proteins. In Figure 5, it may also be observed that the difference in collagen content, as determined by Picrosirius Red staining, for the different flow rates is less pronounced than the one observed with the PTA staining.…”
Section: Papantoniou Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…To examine the accuracy of the entire device when exerting loads, the evaluation procedure employed by Hagenmüller et al 42 was adopted. Accordingly, displacement and force were recorded during the compression of commercially available springs (Gutekunst + Co. KG, Metzingen, Germany).…”
Section: B Evaluation Of System Performancementioning
confidence: 99%
“…Highly and less ordered b-sheets are connected by amorphous network chains [11]. SF is a widely used scaffold material for bone tissue engineering (TE) applications [12][13][14][15][16], due to its excellent biocompatibility [17], controllable degradation [18] and favorable mechanical properties [19]. SF is an interesting scaffold material for bone TE consid- ering its ability to regulate the formation of HA nanocrystals when exposed to simulated body fluid (SBF).…”
Section: Introductionmentioning
confidence: 99%